Towards Modern Slavic Studies aneb snaha o jiné pojetí studia slovanských filologií - Irena Bogoczová; Simona Mizerová; Jiří Muryc (Studia Slavica)
An international team of Slavists from three European countries (Poland, Czechia, Northern Macedonia) worked in 2020–2022 on the project “Towards Modern Slavic Studies”, which brings a new perspective in the implementation of modern Slavic studies programmes in postgraduate studies. The activities of the project are mainly focused on enhancing the skills and competences of students of Slavic Philology and on promoting the internationalisation of higher education. The project has developed an international Slavic studies programme that is characterised by an interdisciplinary focus and, in addition to knowledge, skills and competences in language, literature, culture and translation, equips graduates with a solid knowledge of contemporary social and economic life in the countries covered by the programme.